Thermodynamically stabilized β-CsPbI₃–based perovskite solar cells with efficiencies >18 - Wang, Yong; Dar, M. Ibrahim; Ono, Luis K.; Zhang, Taiyang; Kan, Miao; Li, Yawen; Zhang, Lijun; Wang, Xingtao; Yang, Yingguo; Gao, Xingyu; Qi, Yabing; Grätzel, Michael; et al. (Science (American Association for the Advancement of Science), 2019)
Although β-CsPbI₃ has a bandgap favorable for application in tandem solar cells, depositing and stabilizing β-CsPbI₃ experimentally has remained a challenge.We obtained highly crystalline β-CsPbI₃ films with an extended spectral response and enhanced phase stability. Synchrotron-based x-ray scattering revealed the presence of highly oriented β-CsPbI₃ grains, and sensitive elemental analyses—including inductively coupled plasma mass spectrometry and time-of-flight secondary ion mass spectrometry—confirmed their all-inorganic composition. We further mitigated the effects of cracks and pinholes in the perovskite layer by surface treating with choline iodide, which increased the charge-carrier lifetime and improved the energy-level alignment between the β-CsPbI₃ absorber layer and carrier-selective contacts. The perovskite solar cells made from the treated material have highly reproducible and stable efficiencies reaching 18.4% under 45 ± 5°C ambient conditions.